2019
DOI: 10.3390/cells8121616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Glucose-Induced Oxidative Stress on Paraoxonase 2 Expression and Activity in Caco-2 Cells

Abstract: 1) Background: Hyperglycemia leads to several biochemical and physiological consequences, such as the generation of advanced glycation end products (AGEs) and reactive oxygen species (ROS), which are involved in the development of several human diseases. Intestinal cells are continuously exposed to pro-oxidants and lipid peroxidation products from ingested foods, and also to glyco-oxidative damage. It has been reported that free radical generation may be linked to the development of inflammation-related gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 68 publications
6
21
0
1
Order By: Relevance
“…Several studies have shown higher AGEs levels in HG condition [35,36]. As previously demonstrated, intestinal cells are sensitive to glycooxidative stress when exposed to high glucose concentrations [21]. Glyco-oxidative stress was confirmed in this study with an increase of AGEs formation, increase of intracellular ROS production, lipid peroxidation and a decrease of total antioxidant capacity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Several studies have shown higher AGEs levels in HG condition [35,36]. As previously demonstrated, intestinal cells are sensitive to glycooxidative stress when exposed to high glucose concentrations [21]. Glyco-oxidative stress was confirmed in this study with an increase of AGEs formation, increase of intracellular ROS production, lipid peroxidation and a decrease of total antioxidant capacity.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, a growing interest is devoted to molecules able to decrease dicarbonyl stress targeting the glyoxalase system. Our recent study has shown that high glucose concentrations triggers an increase of levels of intracellular ROS, lipid peroxidation and formation of fluorescent AGEs and GA-modified proteins in intestinal cells [21]. In this study we investigated the effect of high glucose chronic exposure on glyco-oxidation and glyoxalase system in intestinal cells.…”
Section: Introductionmentioning
confidence: 96%
“…Many “in vivo” and “in vitro” studies have shown that there is a strong correlation between a hyperglycemia condition and the formation of AGEs [ 40 , 41 ]. As previously demonstrated, intestinal cells are sensitive to glyco-oxidative stress when exposed to high glucose concentrations [ 20 ]. Glyco-oxidative stress was confirmed in this study with an increase of AGEs formation, increase of intracellular ROS production, lipid peroxidation, and a decrease of total antioxidant capacity.…”
Section: Discussionmentioning
confidence: 93%
“…Cellular vitality was measured using Trypan Blue 0.1% exclusion assay. Cells were treated with culture medium containing 25 mM (control cells) or 50 mM glucose (high glucose, HG) concentrations for 1 week [ 20 ], in the absence or in the presence of apple extract containing two concentrations of polyphenols (0.4 mmol GAE/L and 0.8mmolGAE/L) [ 30 , 33 ]. Medium was replaced two times a week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation